Innocence : a novel - Koontz, Dean R. (Dean Ray), 1945- (New York : Bantam Books, 2014)
Foraging for supplies by night in a beautiful but hostile urban world where strangers would kill him on sight, Addison endures a solitary existence before meeting a quicksilver girl engaged in a dangerous duel of wits with a malicious, well-placed enemy.
Keywords: Social isolation -- Fiction; Fantasy fiction; Suspense fiction; Mystery fiction